O językach mniejszościowych na terenie Podkarpacia – Łemkowie i Bojkowie - Kur-Kononowicz, Jolanta (Studia Ukrainica Posnaniensia, 2026)
Current research topics. In the face of the threat of extinction of many minority languages around the world, the need to protect and promote the Lemko and Boyko languages is becoming increasingly relevant. Thematic outline. The language of national minorities living in the Subcarpathia region and activities related to promoting the language and culture of the Lemkos and Boykos are described. The aim of the article is to highlight the similarities and differences between the Lemko language and the Boyko dialect, to compare them with the Polish language and East Slavic languages, and to present initiatives related to preserving the cultural heritage and promoting the Lemko and Boyko dialect. Conclusions. It is shown that despite phonetic, morphological and lexical differences, these languages belong to the same language group. The influence of East, West and South Slavic languages is emphasized. The Lemko language is taught in schools and universities, and is present in scientific publications, press releases, radio broadcasts and in the virtual space. The Boyko dialect, in contrast, is much less researched, but it has recently attracted increasing interest from scientists. The leading role in the promotion of the language and culture is played by the Lemko Culture Open-Air Museum in Zyndranowa and the Museum of Spiritual and Material Culture of the Boykos in Myczków.